The Interplay between Sharia Law, Religious Principles, and Social Justice in the Islamic Tradition - Ismail Saifnazarov; Azamat Mukhtarov; Bekdavlat Aliyev; Vahob Kuchkarov; Dilmurod Ernazarov (Pharos Journal of Theology)
The purpose of this study was to examine the principles of social justice in Islamic law, their normative consolidation in the legislation of Muslim countries, and their compliance with international standards of social protection. The use of content analysis of Islamic texts enabled the identification of key concepts of social justice, including the obligation to redistribute wealth, the protection of vulnerable groups, and the social responsibility of the state. Comparative legal analysis demonstrated that Sharia norms in the field of social protection emphasise mechanisms such as zakat, waqf, and traditional family obligations, whereas international standards are based on a centralised system of social policy supported by state guarantees. An analysis of the legislation of Muslim countries confirmed that Saudi Arabia maintains a traditional model of social support grounded in religious prescriptions, while the United Arab Emirates employs hybrid regulatory models that integrate Islamic principles with modern socio-economic approaches. In Iran, the system of benefit redistribution through bonyads exhibits limited effectiveness due to a lack of transparency and insufficient state oversight. The study revealed significant differences between the regulation of social justice in Islamic law and international legal systems, particularly in approaches to economic equality, social support for women, and principles of social solidarity.